Interaction of genes and microRNA related to the development of prostate cancer (Experimental biology, 2018)
A search for candidate genes and microRNAs associated with the development of prostate cancer was implemented. A database which includes 67 genes associated with the development of prostate cancer was created. The functions of genes was analyzed in a comparative aspect. Some genes are specific to prostate cancer, many of them are participants in various cancers. Expression of the ASAH1, AURKA, BMI1, EPHB2, GBX2 genes leads to stimulation of malignant growth of prostate cancer cells and can potentially used as therapeutic targets of this cancer. A database of microRNAs associated with the development of prostate cancer was created. Specific features of binding of genes involved in the development of prostate cancer with miRNAs, involved in the development of cancer were determined. According to the calculations, mRNAs of 67 genes involved in the development of prostate cancer are associated with nine miRNAs with a ΔG/ΔGm value more than 90%. Sites are located in CDS, 5'UTR and 3'UTR. Some miRNAs have several target genes involved in the development of prostate cancer. For miR-619-5p, miR-574-3p, miR-3960, miR-1285-3p there are multiple sites with ΔG/ΔGm greater than 90%. miR-619-5p has sites with the highest binding energy of 121 kJ/m with ΔG/ΔGm equal to 100% in mRNA of XIAP gene. It is possible binding miR-619-5p with mRNA of AURKA, BRCA1, FMN1, IL10, MYO6, UHRF1BP1 genes, responsible for the development of prostate cancer with a ΔG/ΔGm equal to 98%.Key words: prostate cancer, gene, microRNA, mRNA, diagnostics.
Keywords: microRNA; mRNA; prostate cancer